Water management of olive trees (Olea europaea L.) in a hilly environment of Central-South Italy - Lavini A.; D'Andria R.; Patumi M.; Morelli G.; Tognetti R.; Sebastiani L. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
Olive tree is one of the most tolerant species to water stress. The experiment was carried out in Italy on five olive cultivars: Ascolana tenera, Nocellara del Belice, Itrana Maiatica e Kalamata. Four irrigation treatments were compared: a not irrigated control, a treatment fully irrigated during all season and two deficit irrigation levels that received an amount of water of 33 and 66 percent of ETc from pit hardening stage to fruit veraison. Results showed that a complete replacement of ETc would result in an averaged yield increase of 20 percent in comparison with 66 percent, though applying up to two times the seasonal water amount. So starting irrigation at the pit hardening stage supplying the crop with an amount of water of 66 percent of ETc is feasible for a water saving strategy in this experimental environment. The yield increase was primarily due to the higher fruit weight according to the enhancement in irrigation volume. Yield of the two years was off for all cultivars probably for the high density of plantation that caused difficulties in air circulation. Plantation density was planned under the hypothesis to cut one plant after another within the row after 15-18 years to obtain a final density of 277 plant ha-1.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)